Identification of new sources of resistance to RHBV- rice hoja blanca virus - Cruz Gallego, Maribel; Rebolledo, María Camila; Cuásquer, Juan B.; Cruz, Daniel Felipe; Peña-Fernández, Alexandra Lorena; Quintero, Constanza; Silva Córdoba, Alexander; Álvarez, María Fernanda; Jojoa-Cruz, Sebastián; Lorieux, Mathias; Stuart, Jeffrey J.; Correa, Fernando (Universidad Nacional de Colombia, 2018)
With the aim to find new sources of resistance to rice hoja blanca (white leaf) disease, transmitted by the insect Tagosodes orizicolus, 660 genotypes were evaluated under greenhouse and field conditions. Seven resistant genotypes were identified, and genomic studies were performed to demonstrate that the resistance in these sources is genetically different from that of Fedearroz 2000, which is currently the variety with the most resistance to hoja blanca. These new resistance sources constitute a resource that can be used to sustainably extend hoja blanca disease management throughout all of the rice-growing regions of tropical America. This is the first report of hoja blanca resistance in indica rice and different from that of Fedearroz 2000.